How Sexualised Images in Advertisements Influence the Attention and Preference of Consumers with a Modern View - Pentus, Kristian; Ruusu, Mariia; Kuusik, Andres; Dorokhova, Liudmyla; Ploom, Kerli (Organizations and Markets in Emerging Economies, 2023)
This paper aims to determine how using sexualised images in advertisements influences the attention and preference of consumers with a modern attitude towards gender stereotypes. This research used a methodological approach based on eye tracking of the perception of advertising images – an eye-tracking study measured how the general attitudes towards gender roles mediate attention. A control question for attitudes towards gender stereotypes was used. The degree of preference for advertising was also examined in the study. The results show that sexual stimuli are not more eye-catching than non-sexual, as sexual advertisements do not capture attention faster and are not viewed for a longer time than non-sexual advertisements. The originality and value of the study lies in the fact that the article supports the right marketing decisions to overcome gender stereotypes in advertising, to avoid advertising errors associated with unjustified sexualisation and eroticisation of visual advertising images and models. It also suggests directions for future research on various aspects of gender stereotypes in advertising.